PREGNANCY AND CHILDBIRTH OUTCOME AFTER A CLOSED COMPLICATED VERTEBRAL COMPRESSION FRACTURE - Alla A. Borshcheva (Кубанский научный медицинский вестник, 2019)
The aim was to analyze the course of pregnancy and childbirth in a woman after a severe spinal injury.Materials and methods. A patient, who became pregnant after a severe spinal injury, was examined and provided with obstretric aid. Her medical documents (medical history) and an individual card of the pregnancy course were examined.Results. The outcome of pregnancy and childbirth was determined for the patient and the fetus after a severe spinal injury.Conclusion. This case demonstrated the course of pregnancy and childbirth in a patient with serious complications arising from a spinal injury. However, despite the severe extragenital pathology, and thanks to the efforts of relevant specialists, the patient endured the pregnancy and was delivered by cesarean section at 37 weeks of gestation, with the birth of a live fullterm newborn. Patients with post-traumatic changes of the musculoskeletal system should be allocated to a separate risk group. Such pregnant women should be subject to a thorough examination in the early stages of pregnancy by a traumatologist and a neurologist, as well as, if indicated, by other specialists. The management tactics of this category of women during pregnancy and childbirth should be strictly individualized.Conflict of interest: the author declares no conflict of interest.